Does meditation training promote pro-environmental behavior? A cross-sectional comparison and a randomized controlled trial. (December 2022) - Riordan, Kevin M.; MacCoon, Donal G.; Barrett, Bruce; Rosenkranz, Melissa A.; Chungyalpa, Dekila; Lam, Sin U; Davidson, Richard J.; Goldberg, Simon B.
Abstract: Meditation training may promote pro-environmental behavior and related variables, though limited research has tested this experimentally. We investigated whether short- or long-term meditation training were associated with pro-environmental behavior, environmental attitudes, and sustainable well-being (i.e., well-being per unit consumption). In a cross-sectional comparison, long-term meditators ( n  = 31; mean = 9154 meditation hours) displayed greater environmental attitudes ( d  = 0.63) but not pro-environmental behavior or sustainable well-being compared to meditation-naïve participants ( d s = -0.14–0.27). In a randomized controlled trial ( n  = 125), eight-week training in Mindfulness-Based Stress Reduction did not significantly improve target variables relative to waitlist or structurally-matched active control ( d s = −0.38–0.43). However, relative to waitlist, randomization to either meditation or active control predicted increases in pro-environmental behavior ( d  = −0.40) and sustainable well-being ( d  = 0.42), although the latter finding was not robust to multiple imputation. While meditation training may promote pro-environmental behavior and its antecedents, the training investigated here does not appear to be uniquely effective. Highlights: Long-term meditation training may increase environmental attitudes. Long-term meditation training is not associated with pro-environmental behavior. Short-term mindfulness training does not improve sustainability-related variables. Active interventions may increase pro-environmental behavior relative to waitlist.